If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -16 + 8y = -4 Reorder the terms: -16 + 4t + 8y = -4 Solving -16 + 4t + 8y = -4 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 4t + 16 + 8y = -4 + 16 Reorder the terms: -16 + 16 + 4t + 8y = -4 + 16 Combine like terms: -16 + 16 = 0 0 + 4t + 8y = -4 + 16 4t + 8y = -4 + 16 Combine like terms: -4 + 16 = 12 4t + 8y = 12 Add '-8y' to each side of the equation. 4t + 8y + -8y = 12 + -8y Combine like terms: 8y + -8y = 0 4t + 0 = 12 + -8y 4t = 12 + -8y Divide each side by '4'. t = 3 + -2y Simplifying t = 3 + -2y
| -4n-40=79-2n+2 | | -8n+4(2+5n)=-6n-14 | | 7a-3=4+6a | | y=(1/2)/(6/18) | | 9x^2+24x+9=0 | | 90-(5x+10)=90-(x+2) | | 5x^2+x-10=0 | | 63-3x=11-9x | | 0x+11=71-3x | | 5x-94=2x-7 | | 4x-8-2x=x-2 | | 5(4-3)=19 | | 2(5-4)=2 | | 6x+2x^2+1=1 | | 2(30-12)=18 | | 4a^2+625b^4=0 | | 4n+55=8 | | x^4-4x^2+1=0 | | 26=6 | | 14-10x=36-24x | | 8x^4+28x^3-30x^2+11x-2=0 | | 3(6x-14)=12x+6(x-3) | | 1x+10=91+x | | 3(15+2x)-60+9x=0 | | 1.875x+2.125y=97.1 | | 2x+1/3=17 | | 2x+4d+6x-5c+4f= | | (x^2+x)(x+6)=7x | | 10x+30=8x+20 | | 2y-30=0 | | y=400+.25(0) | | y=400+.25(-1600) |